"Single‐pot" approach towards the preparation of alkyl and polyfluoroalkyl organo‐silica monolithic capillaries for reversed‐phase liquid chromatography. Issue 19 (16th August 2018) - Narciso Meirelles, Lucas; Silva Campos, Thales; Rodriguez, Zulema; Hernandez, Rebecca; Svec, Frantisek; Zajickova, Zuzana
Abstract: Organo‐silica monolithic capillary columns were prepared using thermally initiated polymerization of mixtures containing 3‐(methacryloyloxy)propyltrimethoxysilane as the silicon‐containing monomer, an aqueous acid catalyst, ethylene dimethacrylate as the cross‐linker, a functional monomer selected from the group comprising octadecyl methacrylate, trifluoroethyl methacrylate, pentafluoropropyl methacrylate, and heptadecafluorodecyl methacrylate, toluene as the porogen, and 2, 2′‐azobisisobutyronitrile as the initiator. The permeability of the monoliths was controlled by varying the composition of the polymerization mixture. Chromatographic properties of resulting monolithic 100 μm i.d. capillaries were evaluated utilizing four sets of probe compounds under isocratic elution conditions in the reversed‐phase mode. Baseline separation of alkylbenzenes and the best steric selectivity were achieved using the octadecyl methacrylate monolithic column verifying that its surface was the most hydrophobic. In contrast, separation of a mixture containing polar compounds was observed using columns prepared in the absence of the functional monomer due to the presence of residual surface silanols at the pore surface. Polyfluoroalkyl stationary phases, especially those with a high number of fluorine atoms, exhibited the highest selectivity towards fluorine‐containing analytes.